Developing Digital Competence Through Total Station and Laser Waterpass Training for Teachers and Students of SMKN 1 Bukittinggi - Yaumal Arbi; M. Giatman; Ari Syaiful Rahman Arifin; Totoh Andayono (Universitas Negeri Padang, 2025)
Modern surveying technologies, including Total Station and Laser Waterpass, are essential in construction and surveying activities. However, SMKN 1 Bukittinggi still faces limited access to digital surveying instruments and limited structured training. This community service program aimed to improve the competence of teachers and students in operating digital measuring instruments through theoretical instruction, simulation, field practice, data analysis, and pretest-posttest evaluation. The implementation stages included coordination with the partner school, preparation of training modules, introduction to instrument principles, hands-on measurement activities, processing of field data using GIS and AutoCAD Civil 3D, mentoring, and program evaluation. The results showed an improvement in participants' conceptual understanding and practical skills. The post-training competency completion rate reached 32%, indicating that the training had a positive effect on participants' digital competence, although additional practice and continuous mentoring are still needed. The program also produced training materials and documentation that can support future learning at the school.